A multi-proxy reconstruction of climate during the late-Pleistocene to early Holocene transition in the northeastern, USA. (July 2021) - Grigg, Laurie D.; Engle, Kevin J.; Smith, Alison J.; Shuman, Bryan N.; Mandl, Maximilian B.
Abstract: A multiproxy record from Twin Ponds, VT, is used to reconstruct climatic variability during the late Pleistocene to early Holocene transition. Pollen, ostracodes, δ 18 O, and lithologic records from 13.5 to 9.0 cal ka BP are presented. Pollen- and ostracode-inferred climatic reconstructions are based on individual species' environmental preferences and the modern analog technique. Principal components analysis of all proxies highlights the overall warming trend and centennial-scale climatic variability. During the Younger Dryas cooling event (YD), multiple proxies show evidence for cold winter conditions and increasing seasonality after 12.5 cal ka BP. The early Holocene shows an initial phase of rapid warming with a brief cold interval at 11.5 cal ka BP, followed by a more gradual warming; a cool, wet period from 11.2 to 10.8 cal ka BP; and cool, dry conditions from 10.8 to 10.2 cal ka BP. The record ends with steady warming and increasing moisture. Post-YD climatic variability has been observed at other sites in the northeastern United States and points to continued instability in the North Atlantic during the final phases of deglaciation.